Adsorption of methylene blue dye on sodium alginate/polypyrrole nanotube composites - Heybet, Ezgi Nur; Ugraskan, Volkan; Isik, Birol; Yazici, Ozlem (ELSEVIER, 2021)
Nanomaterials have recently come to the fore as potential adsorbents due to their high surface, high efficiency, and adsorption capacity. This study the performance of polypyrrole nanotube incorporated sodium alginate (SA/ PPyNT) on the adsorptive removal of methylene blue dye from an aqueous solution was investigated. Firstly, polypyrrole nanotubes were synthesized by oxidative chemical polymerization. Then, polypyrrole nanotubes were added to the sodium alginate gel and the composite beads were prepared by a crosslinking process in a 3% CaCl2 solution. The composite beads were characterized using Fourier transform infrared-attenuated total reflectance (FTIR-ATR), scanning electron microscope (SEM), and atomic force microscopy analyzes. In the adsorption studies, to determine the optimum conditions, experiments were carried out at different conditions namely temperature (25-45 degrees C), contact time, initial pH (2-12), adsorbent dosage (1-5 g/L), dye concentrations (10-50 mg/L). The studies indicated that the removal percentage of MB reached up to 90.5% at pH = 7 and 25 degrees C. Furthermore, different isotherm models such as Freundlich, Langmuir, D-R, and Harkins-Jura were applied. Considering the correlation coefficients, the Langmuir isotherm model was found to be the most suitable model (r(2) = 0.9974). The adsorption capacity showed the maximum at 666.7 mg/g in pH = 7 at 25 degrees C. As a result of the kinetic studies, it was seen that adsorption followed the pseudo-second-order kinetic model (r(2) = 0.9976). When thermodynamic parameters were examined, it was seen that the adsorption occurred exothermically (Delta H-A = - 68.1 kJ/mol) and spontaneously (Delta G(A)(298) = - 27.4 kJ/mol). From the data obtained, it was concluded that the SA/PPyNT composites are promising material as an adsorbent.
Keywords: Polypyrrole; Sodium alginate; Methylene blue; MANGOSTEEN PEEL WASTE; AQUEOUS-SOLUTION; ACTIVATED CARBON; EFFICIENT REMOVAL; METAL-IONS; ALGINATE; ADSORBENT; KINETICS; EQUILIBRIUM; Biochemistry & Molecular Biology; Chemistry; Polymer Science